Terahertz magnetoconductivity of excitons and electrons in quantum cascade structures - Lloyd-Hughes, J; Beere, H; Ritchie, D; Johnston, M (2008)
We examined the quasiparticles formed by the photoexcitation of GaAsAlGaAs terahertz quantum cascade structures using terahertz time-domain spectroscopy. At low temperature and excitation density the measured conductivity was excitonic, with a 1s-2p transition energy indicative of three-dimensional excitons correlated across the quantum well barriers. Free electrons increasingly dominated the conductive response at higher lattice temperatures and excitation densities. Under an external magnetic field transitions from the 1s level into 2p states with different magnetic quantum number were observed, while at high excitation densities the electron cyclotron resonance became more prominent. © 2008 The American Physical Society.